Role-Playing for Rehabilitation: Enhancing Empathy Among Juveniles in Correctional Facilities - Permatasari, Nina; Arsyad, Muhammad; Setiawan, Muhammad Andri; Putro, Hendro Yulius Suryo; Riva’i, Muhammad Fajar; Widyanti, Wiwik (Buletin Konseling Inovatif, 2025)
This study examines the effectiveness of role-playing-based counseling services in enhancing empathy among children at Juvenile Rehabilitation Center Class I Martapura. Employing a quantitative approach, the research utilized a one-group pre-test post-test experimental design to measure changes in empathy levels before and after the intervention. A total of 32 children participated in the study. Data were collected using two instruments: the Empathy Scale and the Role-Playing Engagement Questionnaire. The intervention consisted of structured role-playing sessions designed to improve both cognitive and affective components of empathy. Data analysis using paired sample t-tests revealed a statistically significant increase in empathy scores, with the mean score rising from 151.53 to 157.34 (p < 0.05). These results suggest that role-playing shows promise as an effective method for enhancing empathy in juvenile rehabilitation settings. The findings underscore the potential of integrating experiential learning strategies into psychosocial interventions for institutionalized youth. Further research is recommended to examine contextual and individual factors that may influence the impact of such interventions.